ISOLATION AND CHARACTERIZATION OF A MOLYBDENUM-REDUCING AND PHENOLIC- AND CATECHOL-DEGRADING Enterobacter sp. STRAIN SAW-2 - Mohd Khalizan Sabullah; Mohd Fadhil Rahman; Siti Aqlima Ahmad; Mohd Rosni Sulaiman; Mohd Shukri Shukor; Azlan Jualang Gansau; Nor Aripin Shamaan; Mohd Yunus Shukor (BIOTROPIA, 2017)
Molybdenum is an emerging pollutant worldwide. This study aimed to isolate a molybdenum-reducing bacterium capable of growing on phenolic compounds, specifically phenol and catechol. The screening process was conducted using a microplate assay. The bacterium reduced molybdenum in the form of sodium molybdate to molybdenum blue (Mo-blue). Optimal molybdate reduction occurred within a narrow pH range of 6.3–6.8 and at temperatures between 34–37 °C. Glucose was the most effective carbon source supporting molybdate reduction, while phenol and catechol did not support the reduction process. Additional requirements for molybdate reduction included sodium molybdate concentrations of 15–30 mM and phosphate at 5.0 mM. The Mo-blue produced exhibited an absorption spectrum characterized by a shoulder at 700 nm and a maximum peak near the infrared region at 865 nm. The Mo-reducing bacterium was partially identified as Enterobacter sp. strain Saw-2. The ability of this bacterium to grow on toxic phenolic compounds and detoxify molybdenum suggests strong potential for use in bioremediation applications.